To save succeeding generations from the scourge of war : Jan Christian Smuts (1870 - 1950) and the genesis of international organisation and human rights - Heyns, C.H. (Christof H.) (University of Pretoria, 2016)
Thesis (LLD)--University of Pretoria, 2015.